PENGARUH PENAMBAHAN BUAH NENAS DAN GARAM DENGAN KONSENTRASI YANG BERBEDA DALAM PEMBUATAN KECAP IKAN LAYANG DECAPTERUS SP TERHADAP TOTAL COLONI BAKTERI - Nurfadilah Nurfadilah (Jurnal Pengolahan Pangan, 2018)
Flying fish (Decapterus Sp.) Is one of the by-products that is still underutilized into processed products that have economic value, even though the potential is quite high. Processing of fish with a fermentation process has several products, one of which is the manufacture of fish sauce. While the addition of salt can maintain the shelf life of fish sauce This study aims to determine the comparison of the number of bacterial colony found in Decapterus Sp overcooked fish sauce treated with pineapple and salt. This research was conducted at the Applied Laboratory of Marine Products Processing Technology and at the Basic Polytechnic Laboratory of Palu. The method used in this research is descriptive analysis method. Bacterial identification and business analysis are carried out qualitatively and quantitatively. The highest number of microbes was obtained in fish sauce without using 10% pineapple and 7% salt which was 2.2 x 105 and the lowest was found in fish sauce using 10% pineapple and 7% salt which was 0.3 x 105 and for feasible economic analysis to be marketed because it still has a profit of Rp. 1,900. the conclusion is that fish sauce that uses 10% pineapple and 7% salt is suitable for consumption and marketing and suggestions for further testing for the shelf life of flying fish sauce are added 10% pineapple and 7% salt.